Aboveground Biomass of Wetland Vegetation Under Climate Change in the Western Songnen Plain - Wang, Yanji; Shen, Xiangjin; Tong, Shouzheng; Zhang, Mingye; Jiang, Ming; Lu, Xianguo (Frontiers in Plant Science, 2022)
Understanding the spatiotemporal dynamics of aboveground biomass (AGB) is crucial for investigating the wetland ecosystem carbon cycle. In this paper, we explored the spatiotemporal change of aboveground biomass and its response to climate change in a marsh wetland of western Songen Plain by using field measured AGB data and vegetation index derived from MODIS datasets. The results showed that the AGB could be established by the power function between measured AGB density and the annual maximum NDVI (NDVImax) of marsh: Y = 302.06 × NDVImax1.9817. The averaged AGB of marshes showed a significant increase of 2.04 g•C/m2/a, with an average AGB value about 111.01g•C/m2 over entire western Songnen Plain. For the influence of precipitation and temperature, we found that the annual mean temperature had a smaller effect on the distribution of marsh AGB than that of the total precipitation in the western Songnen Plain. Increased precipitation in summer and autumn would increase AGB by promoting marshes vegetation growth. In addition, we found that the minimum temperature (Tmin) and maximum temperatures (Tmax) have an asymmetric effect on marsh AGB on the western Songnen Plain: warming Tmax has a significant impact on AGB of marsh vegetation, while warming at night can non-significantly increase the AGB of marsh wetland. This research is expected to provide theoretical guidance for the restoration, protection and adaptive management of wetland vegetation in the western Songnen Plain.